Rational design of single-ion magnets and spin qubits based on mononuclear lanthanoid complexes - Baldoví, José J; Cardona-Serra, Salvador; Clemente-Juan, Juan M; Coronado, Eugenio; Gaita-Ariño, Alejandro; Palii, Andrew (Inorganic chemistry, 2012)
Here we develop a general approach to calculating the energy spectrum and the wave functions of the low-lying magnetic levels of a lanthanoid ion submitted to the crystal field created by the surrounding ligands. This model allows us to propose general criteria for the rational design of new mononuclear lanthanoid complexes behaving as single-molecule magnets (SMMs) or acting as robust spin qubits. Three typical environments exhibited by these metal complexes are considered, namely, (a) square antiprism, (b) triangular dodecahedron, and (c) trigonal prism. The developed model is used to explain the properties of some representative examples showing these geometries. Key questions in this area, such as the chemical tailoring of the superparamagnetic energy barrier, tunneling gap, or spin relaxation time, are discussed. Finally, in order to take into account delocalization and/or covalent effects of the ligands, this point-charge model is complemented with ab initio calculations, which provide accurate information on the charge distribution around the metal, allowing for an explanation of the SMM behavior displayed by some sandwich-type organometallic compounds.